Serviceability and Flexural Behavior of Concrete Beams Reinforced with Basalt Fiber-Reinforced Polymer (BFRP) Bars Exposed to Harsh Conditions - Alkhraisha, Hakem (Polymers (Basel), 2020)
The main objective of this study was to investigate experimentally and numerically the behavior of basalt fiber-reinforced polymer (BFRP) reinforcement exposed to a combination of ultraviolet rays, humidity, and rain. Specifically, the effects of the previously stated harsh exposure on the serviceability performance and flexural capacity of BFRP reinforced concrete beams was examined. Holding the exposure parameter constant, the study also evaluated the effects of reinforcement ratio and beam detailing on the flexural capacity and the bond-dependent coefficient (k(b)) of the beams. Seven beams were cast and tested, four of which were reinforced with exposed BFRP bars, two were reinforced with unexposed BFRP bars, and one specimen was cast and reinforced with steel bars to serve as a benchmark specimen. The results indicate that the k(b) factor was averaged to be 0.61 for all the beams. Test results also indicate that increasing the reinforcement ratio did not result in a directly proportional increase in the moment capacity. The period of exposure did not cause any significant impact on the behavior of the over-reinforced beams. Thus, a finite element model was created to simulate the impact of exposure on the behavior of under-reinforced BFRP reinforced concrete beams.